Solution
- The general equation of a circle is given by:
![\begin{gathered} (x-a)^2+(y-b)^2=r^2 \\ \text{where, } \\ \text{The center of the circle is at point }(a,b) \\ \text{The rad}ius\text{ of the circle is }r \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/khxqu2uiv2sh1a8bpbm9x5go2jyrtvzmn6.png)
- Since the center of the circle is at (-8, 9), then it implies that
![\begin{gathered} a=-8 \\ b=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4apemhz7n4mtmehtvuybkpzyvb81rruysr.png)
- Thus, we can write the equation as follows
![\begin{gathered} (x-(-8))^2+(y-9)^2=r^2 \\ (x+8)^2+(y-9)^2=r^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ywx0x9buft9095s6qjhnlm57ewv81hl14z.png)
- As it is, the equation is still incomplete because we don't have the radius (r).
- This radius can be gotten by applying the condition given in the question that "The circle passes through the origin" .
- This means that the circle, when drawn, passes through the point (0, 0).
- Thus, we can substitute x = 0 and y = 0 into our incomplete equation and find the value of r.
- This is done below:
![\begin{gathered} (x+8)^2+(y-9)^2=r^2 \\ \\ \text{put }x=0,y=0 \\ \\ (0+8)^2+(0-9)^2=r^2 \\ 8^2+9^2=r^2 \\ r^2=64+81 \\ r^2=145 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sbtzicqb65p2dgybw9lbf0ofw87bdcft28.png)
- Thus, the equation of the circle with center (-8, 9) is:
![(x+8)^2+(y-9)^2=145](https://img.qammunity.org/2023/formulas/mathematics/college/fpe9cpwqsfpj6zbec03cutpll2ygbdco96.png)
Final Answer
The answer is
![(x+8)^2+(y-9)^2=145](https://img.qammunity.org/2023/formulas/mathematics/college/fpe9cpwqsfpj6zbec03cutpll2ygbdco96.png)